Improved potassium reliability in whole blood through hemolysis detection on the novel GEM Premier 7000 blood gas analyzer: Hemolysis detection on GEM Premier 7000 - Lippi, Giuseppe; Pighi, Laura; Salvagno, Gian Luca; Marcazzan, Filippo; Rizza, Mariateresa (Journal of Medical Biochemistry, 2025)
Background: Hemolysis is the most frequent preanalytical error in clinical laboratories, but its detection in point-of-care (POC) settings remains challenging due to the lack of sample separation. This study was planned to validate the hemolysis index (HI) threshold of GEM Premier 7000 blood gas analyzer for detecting hemolysis levels that may generate clinically significant interference in potassium measurement. Methods: Heparinized whole blood samples were collected from healthy volunteers and divided into six aliquots; one was used as non-hemolyzed control, while hemolysis was mechanically induced in the remaining five aliquots by repeated aspirations through a fine-gauge needle. HI and potassium were measured on GEM Premier 7000. Results: The final study population consisted in 18 volunteers. Both HI and potassium levels increased progressively and significantly with the number of fine-needle aspirations (p<0.001 for both). A strong positive correlation was observed between HI values and percentage increases in potassium concentration in hemolyzed aliquots (r=0.985, p<0.001). Receiver operating characteristic (ROC) curve analysis confirmed excellent diagnostic accuracy of HI in detecting potassium increases above the total 7.4% allowable error threshold, with an area under the curve (AUC) of 1.00 and optimal cutoff of 102 mg/dL (0.94 sensitivity and 1.00 specificity). At the manufacturer-recommended 116 mg/dL threshold, the AUC was 0.95, with 0.89 sensitivity and 1.00 specificity. Conclusions: These results confirm that the novel GEM Premier 7000 blood gas analyzer provides accurate detection of hemolysis thresholds in whole blood that may impair potassium test reliability.